Analysis of current running sock structures with regard to blister prevention - Baussan, E; Bueno, MA; Rossi, RM; Derler, S (Textile research journal, 2013)
In this paper, in-shoe blister formation during running is analyzed and possibilities to reduce these cutaneous lesions by appropriate sock properties are discussed. Six types of cotton-made athletic socks were studied in order to evaluate the influence of the knitted structure on the sock-to-skin friction (terry jersey, plain jersey, and non-raised jersey duffel structures). The contact conditions between a running shoe and foot areas prone to friction blisters were simulated using a linear reciprocating tribometer, and the friction behavior of the socks in contact with a mechanical skin model was investigated. In additional experiments, the shock absorption properties of the socks were measured. Among the investigated socks, the terry jersey fabric knitted in a specific process and a dense, tight jersey structure, i.e. a plain jersey knitted with two yarns, were found to be most suitable for running socks.